"The Connection Itself was the Project" : Capstone Experiences for Emerging Professional Musicians Through WIL. - Yeo, Narelle; Mohler, Sophie; Paxton, Ines; Kwan, Helen Hoi Ting; Massey, Lachlan; Hallworth, Thomas (Student Success v.13 n.3 p.37-45 https://doi.org/10.5204/ssj.2484, 2022)
During their studies, musicians transition to work-readiness, develop a professional persona and graduate from skills acquisition in a traditional master-mentor relationship towards heterarchical collaboration in ensembles. Over the final year of an undergraduate program in performance, students, faculty/industry mentors and course coordinators worked collaboratively to implement a music work integrated learning (WIL) project, culminating in public performance as a capstone experience. This phenomenological case report outlines how a student group with diverse skills formed a complex adaptive system through inclusion, connection, support, and collaboration culminating in a final public performance and this practice report. Through this process, students obtained a broad range of graduate skills as well as professional musical competencies within a functioning heterarchy. In creative and performing arts, WIL can positively produce professional outcomes that appear indistinguishable from professional practice in the industry at large. This can be a model for transformative WIL in other disciplines. In addition, this research and practice report was prepared primarily by students with a faculty mentor, providing yet another set of graduate skills to musicians seeking portfolio careers in the arts. [Author abstract]